2020
DOI: 10.1088/2515-7655/ab67e2
|View full text |Cite
|
Sign up to set email alerts
|

Testing fuel cell catalysts under more realistic reaction conditions: accelerated stress tests in a gas diffusion electrode setup

Abstract: Gas diffusion electrode (GDE) setups have very recently received increasing attention as a fast and straightforward tool for testing the oxygen reduction reaction (ORR) activity of surface area proton exchange membrane fuel cell (PEMFC) catalysts under more realistic reaction conditions. In the work presented here, we demonstrate that our recently introduced GDE setup is suitable for benchmarking the stability of PEMFC catalysts as well. Based on the obtained results, it is argued that the GDE setup offers inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 45 publications
4
87
0
Order By: Relevance
“…In a recent work we showed that ASTs can be performed in our GDE setup but the used catalyst loading was comparable to loadings for RDE measurements and hence far from realistic fuel cell loadings. 15 In the present work, the catalyst film on the GDL (i.e. the GDE) is prepared by vacuum filtration as described by Yarlagadda et al 21 4 In the SI it is demonstrated that with the established procedure, reproducible particle size distributions of the different Pt/C catalysts could be determined before ( Figure S5) as well as after the ASTs (Figure S6).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In a recent work we showed that ASTs can be performed in our GDE setup but the used catalyst loading was comparable to loadings for RDE measurements and hence far from realistic fuel cell loadings. 15 In the present work, the catalyst film on the GDL (i.e. the GDE) is prepared by vacuum filtration as described by Yarlagadda et al 21 4 In the SI it is demonstrated that with the established procedure, reproducible particle size distributions of the different Pt/C catalysts could be determined before ( Figure S5) as well as after the ASTs (Figure S6).…”
Section: Resultsmentioning
confidence: 91%
“…In contrast, the GDE setup provides more realistic conditions than the RDE method but is at the same time a more simple and faster methodology than flow cell or MEA measurements. 14,15 Several repeats of the measurements can be performed and their reproducibility be discussed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, we investigate the degradation of Pt/C catalysts in alkaline conditions under more realistic reaction conditions as compared to conventional electrochemical cells where the catalyst is exposed to an aqueous electrolyte. Instead, a gas diffusion electrode (GDE) setup [13][14][15] is employed, which has been used recently to study the stability of carbon-supported platinum catalysts in acidic media 16 . To obtain alkaline conditions, for the present study the Nafion membrane from a PEMFC has been replaced with an anion exchange membrane (AEM) and an alkaline ionomer was mixed into the catalyst layer.…”
Section: Introductionmentioning
confidence: 99%